(untitled) (Bangladesh Journal of Medical Science, 2020)
Objective: Lung cancer is one of the most common cancers. Previous studies findings are not suitable to explain symptom experience and symptom management of Bangladeshi persons with lung cancer. This study was aimed to identify the symptom experiences and determines the management strategies among persons with lung cancer. Methods: A descriptive study design, using combined both quantitative and qualitative research methods, was chosen for this study. Convenient sampling was used to recruit 382 persons with lung cancer from two public and two private tertiary hospitals and 16 participants were invited for an in-depth interview in the qualitative part. Data collection was conducted from October 2015 to July 2016, using the MD Anderson Symptom Inventory Lung Cancer (MDASI-LC) questionnaire and using a semistructured interview guide to explore their symptom management strategies. The quantitative data were analyzed using descriptive and inferential statistics and qualitative data by content analysis. Results: Pain was the most frequently reported physical symptom and the most severe one, followed by sleep disturbance and fatigue. Psychological symptoms such as sadness and distress were also frequent. Participants also reported other symptoms that interfered with daily living in terms of mood, general activity, work, enjoyment of life, walking and relationships with others. The symptom management consisted of three categories, which were taking modern medicine, adopting complementary therapies, and cultivating mind and body balance. Most of the participants addressed uses of more than one strategy. Conclusions: Participants experienced several physical and psychological symptoms that interfered with their lives. This finding will be beneficial for health care personnel regarding clinical practice to manage symptoms and further research may be conducted to obtain proper interventions to alleviate symptoms, and improve quality of life. Bangladesh Journal of Medical Science Vol.19(3) 2020 p.386-393